MEMBANGUN KELUARGA YANG SUKSES DAN HARMONIS - Riana Friska Siahaan (Universitas Negeri Medan, 2016)
To understand the meaning of marriage we refer to the definition : Marriage is a bond between a woman and a man as husband and wife with the aim to establish a happy and eternal Almighty based family (Marriage Act N0. I / Chapter I Article l RI Constitution) .Wallerstain (1995) revealed that a successful marriage will be the basis of the maturity and the consolidation of sexual identity of each partner should be disclosed. Family is an important organization in human life. Happy family largely depend on the husband and wife. Family happiness will establish and assimilate emotional, social and spiritual children in the family. In addition, a happy family is also encouraging the development of good emotional, social and spiritual behaviour. However, there are many studies showing that families are broken or divorced, or parents who do not work will lead to behavioral, emotional, social problems. There is also a spiritual aspect of dating a youth dreamed to have a harmonious family. Therefore they approach typically seeks to know each other and explore each individual. It thus does establish harmonious family which is a dream of everyone and need to be done as a basis to reach a stage where dreams can come true. Building a harmonious family was not enough just to dream, but it needs to be put on an ongoing basis as a long-term vision of every family till death do them part. Many married couples are still unaware that the harmony in the family did not come suddenly, but must be cultivated and pursued jointly.Kata Kunci : Perkawinan, Keluarga